SLAC: A Formal Service-Level-Agreement Language for Cloud Computing - Uriarte, Rafael Brundo; Tiezzi, Francesco; De Nicola, Rocco (Proceedings of the 2014 IEEE/ACM 7th International Conference on Utility and Cloud Computing, 2014)
The need of mechanisms to automate and regulate the interaction amongst the parties involved in the offered cloud services is exacerbated by the increasing number of providers and solutions that enable the cloud paradigm. This regulation needs to be defined through a contract, the so-called Service Level Agreement (SLA). We argue that the current solutions for SLA specification cannot cope with the distinctive characteristics of clouds. Therefore, in this paper we define a language, named SLAC, devised for specifying SLA for the cloud computing domain. The main differences with respect to the existing specification languages are: SLAC is domain specific, its semantics are formally defined in order to avoid ambiguity, it supports the main cloud deployment models, and it enables the specification of multi-party agreements. Moreover, SLAC supports the business aspects of the domain, such as pricing schemes, business actions and metrics. Furthermore, SLAC comes with an open-source software framework which enables the specification, evaluation and enforcement of SLAs for clouds. We illustrate potentialities and effectiveness of the SLAC language and its management framework by experimenting with an Open Nebula cloud system.